QX-OH/Levobupivacaine: Fixed-dose combination to provide a long-acting postoperative pain of knee surgery in rodents - Zhao, WenLing; Yang, Jun; Zhang, YuJun; Liu, Jin; Zhang, WenSheng (European journal of pharmaceutical sciences, 2018)
Although total knee arthroplasty (TKA) is a commonly performed procedure, anesthetic efficacy in post-surgical pain remains an issue. Exparel (45mM liposome bupivacaine), a relatively long-acting local anesthetic, has shown efficacy in blocking peripheral nerve or periarticular infiltration to achieve better post-TKA analgesia. In the present work, we tested whether a fixed-dose combination of QX-OH (35mM) and levobupivacaine (10mM) (QX-OH/LB) could confer longer-lasting pain relief and reduce periarticular tissue toxicity compared to liposome bupivacaine (45mM) after TKA operation. In the sciatic nerve block, the duration of sensory block by QX-OH/LB was 2-fold higher than by liposome bupivacaine (median [25th, 75th percentiles], 9.83 [9.33, 10.83] hours versus 4.83 [4.83, 5] hours; P=0.001). Liposome bupivacaine failed to improve post-surgical travel distance and speed (P=0.373) in rats 6h after TKA surgery (versus saline). Similar results were observed in operated mice treated with liposome bupivacaine. However, QX-OH/LB increased locomotor activities markedly both in rats and mice at 6h post-TKA (P<0.001). In addition, there was no difference in the inflammatory recruitment and articular structural damage among murine models-treated with QX-OH/LB, liposome bupivacaine and saline. In conclusion, we show that QX-OH/LB is a safe and long-lasting anesthetic than liposome bupivacaine in the post-TKA pain management in murine models. [Display omitted]